Religiosity As a Mediator Variable Influence Between Character Strength and Parent Attachment On The Resilience Of Adolescent Victims Of Earthquake and Tsunami Living On The Coastal, Banten - Natris Idriyani (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to test the fit model of the influence of character strength and parent attachment on resilience mediated by the religiosity of adolescent victims of the earthquake and tsunami who live on the coast. The conceptual used to explain resilience is based on the socio-ecological perspective of Ungar & Liebenberg (2013). Character strength uses the theory of Seligman (2006). The concept of parent attachment is explained based on Armsden and Greenberg's (1987) theory. And the concept of religiosity is based on Fetzer's theory (1999). The measuring instrument used to measure resilience is YCRM, character strength using VIA-IS for youth, parent attachment using IPPA, and religiosity using the religiosity scale. The data analysis technique used in this study was the Structural Equation Model (SEM) with the help of Amos software. The results showed that the model of the influence of character strength and parent attachment on resilience mediated by the religiosity of youth victims of the earthquake and tsunami living on the coast is fit with the data. Religiosity acts as a mediator of the influence variable between character strength and parent attachment on the resilience of adolescent victims of the earthquake and tsunami living on the coast.